Alcohol Consumption and Pancreatitis Mortality - YE Razvodovsky (Annals of Pancreatic Disorders and Treatment - Peertechz Publications, 2017)
Background: Pancreatitis is a major public health problem with high associated economic costs. Accumulated research and empirical evidence suggests that excessive alcohol consumption is a major risk factor for both acute and chronic pancreatitis. In line with this evidence we assume that devastating combination of higher level of alcohol consumption per capita and drinking of vodka results in a close association between binge drinking and pancreatitis mortality at the aggregate level in Russia. This paper was design to estimate the aggregate level effect of binge drinking on pancreatitis mortality rate in Russian. Method: Trends in age-adjusted, sex-specifi c pancreatitis mortality and fatal alcohol poisoning rate (as a proxy for binge drinking) from 1956 to 2015 were analyzed employing a distributed lags analysis in order to ass's bivariate relationship between the two time series. Results: The results of the time series analysis indicates the presence of a statistically significant association between the two time series at zero lag for male (r = 0.72; S.E. = 0.13), and for female (r = 0.36; S.E. = 0.13). Conclusion: The results of present study support the hypothesis that alcohol played a crucial role in pancreatitis mortality fl uctuation in Russia over the past decades. This study also indicates that substantial proportion of pancreatitis deaths in Russia is due to acute effect of binge drinking. The           findings from the present study have important implications as regards pancreatitis mortality prevention indicating that a restrictive alcohol policy can be considered as an effective measure of prevention in countries where higher rate of alcohol consumption and binge drinking pattern.